2021
DOI: 10.1002/ep.13672
|View full text |Cite
|
Sign up to set email alerts
|

How changes in human activities during the lockdown impacted air quality parameters: A review

Abstract: The health emergency linked to the spread of COVID-19 has led to important reduction in industrial and logistics activities, as well as to a drastic changes in citizens' behaviours and habits. The restrictions on working activities, journeys and relationships imposed by the lockdown have had important consequences, including for environmental quality. This review aims to provide a structured and critical evaluation of the recent scientific bibliography that analysed and described the impact of lockdown on huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 160 publications
0
25
0
1
Order By: Relevance
“…Moreover, we used the most recent road noise data available for Germany, but changes in road-traffic patterns over time are possible. With regard to the COVID-19 pandemic, a decrease in road traffic leading to changes in air pollution has been observed by some studies [62]. For example, a decrease in road-traffic volume by 37% and road occupancy by 52% has been shown during the Stay Home Order (SHO) in Washington state [63].…”
Section: Limitationsmentioning
confidence: 99%
“…Moreover, we used the most recent road noise data available for Germany, but changes in road-traffic patterns over time are possible. With regard to the COVID-19 pandemic, a decrease in road traffic leading to changes in air pollution has been observed by some studies [62]. For example, a decrease in road-traffic volume by 37% and road occupancy by 52% has been shown during the Stay Home Order (SHO) in Washington state [63].…”
Section: Limitationsmentioning
confidence: 99%
“…The change by people of their daily behavior and patterns to contain or avoid the virus has not only affected the economy but has also extended to other aspects such as the environment [35][36][37]. During the lockdowns, there was less traffic on the communication routes.…”
Section: Introductionmentioning
confidence: 99%
“…The lockdown brought about drastic impacts at social and economic fronts [28][29][30][31] as well as impacts on the environment, particularly in the context of air quality, environmental, and noise reduction [32][33][34]. To date, previous data and studies have shown that the emergency measures taken by the government to prevent human activities in the lockdown period of COVID-19 had effectively and significantly reduced ambient air pollution [20,[35][36][37][38][39][40][41]. However, no comprehensive investigation has been conducted on the impact of COVID-19 control measures on gaseous and particulate air pollutants in Xi'an.…”
Section: Introductionmentioning
confidence: 99%